L’étrange silence du Nobel Prize Committee sur la « théorie des marchés efficients » - Bernard Guerrien; Ozgur Gun (Revue de la Régulation)
The 2013 “Nobel Prize” in Economic Sciences was awarded to Eugene Fama and Robert Shiller, who are known for their opposing positions on the theory of “efficient financial markets.” Yet in the official prize announcement, the jury fails to mention this “theory,” which is never truly defined. The selection of Fama seems due to the mere fact that he coined the phrase “efficient markets,” an ideologically laden term which has gained widespread acceptance in the world of finance. This despite the fact that, even for a neo-classical economist, “efficient markets,” taken literally, is a nonsensical notion. Rather than to present Fama and Shiller as thinkers with conflicting theories, the jury chose to frame them as complementary: Fama’s contributions pertaining to the short term, Shiller’s dealing with a “longer term.” In reality, both thinkers’ contributions are very limited, even when compared to those of former awardees. Thus this decision confirms that the jury’s principal motivation was to reward – without saying so explicitly – the introduction of the notion of "efficient markets" in finance.